2015
DOI: 10.1016/j.wem.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Traction Splints in Mountain Rescue Prehospital Care: To Use or Not to Use? That Is the Question

Abstract: Femur fractures are rare within mountain rescue. Traction splints may be no more effective than other methods of splinting in prehospital care. We failed to identify evidence that supports the hypothesis that traction splints reduce morbidity or mortality. We advocate the use of a femoral traction splints but recognize that other splints may also be appropriate in this environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Through surveys, ref [45] analyzed the equipment of medical backpacks in MR operations and pointed out several important selection criteria, with a special focus on equipment properties and quality standards. Others have further recognized equipment weight as important in this context [46][47][48]. In detail, ref [46] assessed MR casualty bags using an experimental evaluation process with a special focus on applicability in cold and windy environments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Through surveys, ref [45] analyzed the equipment of medical backpacks in MR operations and pointed out several important selection criteria, with a special focus on equipment properties and quality standards. Others have further recognized equipment weight as important in this context [46][47][48]. In detail, ref [46] assessed MR casualty bags using an experimental evaluation process with a special focus on applicability in cold and windy environments.…”
Section: Related Workmentioning
confidence: 99%
“…Aside from the light weight, the equipment should furthermore be easy to use and be able to transport and feature a high payload. In the usability assessment of specialized medical equipment, ref [48] identified, through questionnaire analysis, the weight of the equipment and the time taken to apply it as important factors for an eventual equipment selection.…”
Section: Related Workmentioning
confidence: 99%
“…None of the identified literature discussed why responders did not apply traction splints when indicated. Despite similarly low rates of application, a survey of pre-hospital practitioners found that they viewed traction splint use as only mildly or moderately problematic, suggesting there is a disconnect between perceptions and practice (18).…”
Section: Inappropriate Applicationmentioning
confidence: 99%
“…To date, there has been no published systematic review on the pre-hospital use of traction splints. Pre-hospital practitioners are infrequently exposed to femoral shaft fractures (18), and despite the wide use of traction splints, there appears to be questions regarding the evidence supporting their use (16). This comprehensive systematic review will attempt to determine if the use of traction splints in the pre-hospital management of patients with femoral fractures reduces the complications compared to traditional splinting.…”
Section: Introductionmentioning
confidence: 99%